2012
DOI: 10.1002/hep.25628
|View full text |Cite
|
Sign up to set email alerts
|

High plasma level of nucleocapsid-free envelope glycoprotein-positive lipoproteins in hepatitis C patients

Abstract: Hepatitis C virus (HCV) particles associate viral and lipoprotein moieties to form hybrid lipoviral particles (LVPs). Cell culture-produced HCV (HCVcc) and ex vivo-characterized LVPs primarily differ by their apolipoprotein (apo) B content, which is low for HCVcc, but high for LVPs. Recombinant nucleocapsid-free subviral LVPs are assembled and secreted by apoB-producing cell lines. To determine whether such subviral particles circulate in HCV-infected individuals, LVPs complexed with immunoglobulin were precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 42 publications
3
43
0
2
Order By: Relevance
“…A mixed population composed of two types of particles was also previously observed by Scholtes et al 24 in the low-density fractions of HCV+ patient plasmas. However, the authors purified LVPs from the low density fractions by protein A-mediated precipitation of viral particles naturally coated with patients’ antibodies.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…A mixed population composed of two types of particles was also previously observed by Scholtes et al 24 in the low-density fractions of HCV+ patient plasmas. However, the authors purified LVPs from the low density fractions by protein A-mediated precipitation of viral particles naturally coated with patients’ antibodies.…”
Section: Discussionsupporting
confidence: 77%
“…This result is consistent with the findings of a study in which the group of André23 characterised hybrid particles produced by Huh-7.5 cells transduced with HCV envelope glycoproteins. Transduction with the genes encoding E1 and E2, in the absence of additional viral genes, is sufficient to induce the assembly and secretion of these defective low-density hybrid particles resembling TG-rich lipoproteins (VLDL/LDL) and bearing the viral glycoproteins on their surface 23 24. As suggested by these authors, many defective particles containing only E1 and E2 are likely to circulate in the bloodstream of chronically infected patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this respect, in vivo data suggesting a strong association between apoB and HCV have been recently revisited. Scholtes and collaborators demonstrated that LVP could mainly be apoB/gpE1-gpE2 positive, but nucleocapsid-free, particles (85). This new subclass of particles could then be defined as defective subviral particles (named eLVP).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is not excluded that infectious HCV particles could harbor only apoE and not apoB. It remains to be determined whether other types of viral or subviral particles, such as eLVP (85), could be produced by HCV-replicating cells. In this respect the HCV-replicating HepG2 line developed here will be instrumental.…”
Section: Discussionmentioning
confidence: 99%